2022
DOI: 10.3390/horticulturae8090806
|View full text |Cite
|
Sign up to set email alerts
|

Improving Aerial and Root Quality Traits of Two Landscaping Shrubs Stem Cuttings by Applying a Commercial Brown Seaweed Extract

Abstract: The availability of quality planting material is one of the most important requirements for increasing the productivity of any ornamental crop. Horticulturists make use of auxins and apply them exogenously to cuttings to generate adventitious roots and balanced shoots. Many studies have illustrated the influence of seaweed extracts on the growth of ornamental crops; their use in vegetative cutting propagation, to our knowledge, has been little investigated. Moreover, there is a lack of information on the influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 78 publications
0
10
2
Order By: Relevance
“…The application of biostimulants based on seaweed extracts in our experiment did not positively influence the number of leaves, chlorophyll index (SPAD) and leaf area index (Table 7). These results are in disagreement with that found in Lantana camara, Abelia x grandiflora [42] and Cornus alba 'Aurea' and 'Elegantissima' [94]. Our preliminary results (Tables 6 and 8) disagree with Ratore et al [95], Kocira et al [96], Gajc-Wolska et al [60] and Caccialupi et al [97] who obtained a positive effect, by applying seaweed extracts, on plant growth, development and yield.…”
Section: Discussioncontrasting
confidence: 87%
See 2 more Smart Citations
“…The application of biostimulants based on seaweed extracts in our experiment did not positively influence the number of leaves, chlorophyll index (SPAD) and leaf area index (Table 7). These results are in disagreement with that found in Lantana camara, Abelia x grandiflora [42] and Cornus alba 'Aurea' and 'Elegantissima' [94]. Our preliminary results (Tables 6 and 8) disagree with Ratore et al [95], Kocira et al [96], Gajc-Wolska et al [60] and Caccialupi et al [97] who obtained a positive effect, by applying seaweed extracts, on plant growth, development and yield.…”
Section: Discussioncontrasting
confidence: 87%
“…A previous study carried out by Loconsole et al [42] proved that Goteo ® improved the aerial and root quality traits of ornamental cuttings at a dose of 3 mL L −1 in wild sage, with a greater number of roots, better growth traits, root morphologies and carbohydrate content compared to IBA. Moreover, in glossy Abelia, the same authors [42] suggested the application of a 1 mL L −1 concentration of Goteo ® to obtain high-quality rooted stem cuttings.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…They are widely used for their multifarious benefits to crop growth and development, to prevent pests and diseases, and to improve the quality of the product and this has been proven time and again in a number of agri-horticultural crops [ 23 , 27 , [45] , [46] , [47] ]. Beside these, seaweed extracts have also been postulated to enhance rooting of cuttings in only a few species, like Passiflora actinia Hook [ 48 ], Pinus patula [ 49 ], Lantana camara and Abelia × grandiflora [ 50 ] and hybrid tea rose [ 51 ] etc. Despite these encouraging characteristics, in our experience, only a small number of seaweed extracts have been studied so far for root promotion in cutting propagation.…”
Section: Discussionmentioning
confidence: 99%
“…Seaweed products sometimes contain many phytohormones necessary for plants, including auxins, gibberellins, and cytokinins, which increase their development [Wang et al 2016]. So far, such preparations have been used mainly for propagating various species of ornamental shrubs [Pacholczak et al 2012, 2016, Monder 2019, Loconsole et al 2022. Biostimulants increase the ability of plants to use nu-trients, improve tolerance to stress factors, contribute to better root system growth, and increase the efficiency of photosynthesis and other metabolic processes in plants [Calvo et al 2014, Rouphael et al 2018].…”
mentioning
confidence: 99%